2003
DOI: 10.1080/13921657.2003.10512540
|View full text |Cite
|
Sign up to set email alerts
|

Winter Diet and Movements of Wolf (Canis Lupus) in Alampedja Nature Reserve, Estonia

Abstract: Wolf (Canis lupus) diet was studied in Alam-Pedja Nature Reserve from October to April 19992001. 119 wolf scats were collected and analysed. Remains of eight mammal species were found in wolf scats of which ungulates formed nearly 80%. Wolf diet in the nature reserve consisted mainly of wild boar (Sus scrofa; 37%), moose (Alces alces; 30.5%) and roe deer (Capreolus capreolus; 12.1%). A proportion of moose in ungulate biomass was calculated to be 77.5%; wild boar 20.4% and roe deer only 2%. It was found that wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
1
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 17 publications
1
9
1
1
Order By: Relevance
“…Studies in eastern and central Europe agree that wolves hunt for wild or domestic ungulates (i.e. Jędrzejewski et al, 2000;Kübarsepp and Valdmann, 2003;Sidorovich et al, 2003;Andersone and Ozolins, 2004;Gazzola et al, 2005;Nowak et al, 2005;Hovens and Tungalaktuja, 2005) depending on game abundance (Meriggi et al, 1991;Mattioli et al, 1995;Sidorovich et al, 2003). But unlike our results from German wolves, who primarily hunt on roe deer, most of the other studies confirmed the wolf hunt preferably on the largest ungulate species in high abundance, available in the region.…”
Section: Diet Compositioncontrasting
confidence: 71%
“…Studies in eastern and central Europe agree that wolves hunt for wild or domestic ungulates (i.e. Jędrzejewski et al, 2000;Kübarsepp and Valdmann, 2003;Sidorovich et al, 2003;Andersone and Ozolins, 2004;Gazzola et al, 2005;Nowak et al, 2005;Hovens and Tungalaktuja, 2005) depending on game abundance (Meriggi et al, 1991;Mattioli et al, 1995;Sidorovich et al, 2003). But unlike our results from German wolves, who primarily hunt on roe deer, most of the other studies confirmed the wolf hunt preferably on the largest ungulate species in high abundance, available in the region.…”
Section: Diet Compositioncontrasting
confidence: 71%
“…Apart from the Italian Apennines (Mattioli et al 1995;Ciucci et al 1996;Meriggi et al 1996Mattioli et al 2004), a similar result was found only in a few other locations of Eastern Europe like Estonia (Kübarsepp and Valdmann 2003), Russia (Rusakov andTimofeeva 1984 in Okarma 1995) and Belarus (Sidorovich et al 2003).…”
Section: Prey Use and Dietary Responsementioning
confidence: 60%
“…The diet of wolves in Latvia is rather diverse although they mainly preyed upon wild ungulates as in other areas where the natural prey base is rich (Bibikov, 1985;Jędrzejewska & Jędrzejewski, 1998;Kübarsepp & Valdmann, 2003;Mech 2003). Consumption of beaver is mentioned also in other studies of wolves (Pavlov, 1990;Kohira & Rexstad, 1997;Jędrzejewska & Jędrzejewski, 1998;Valdmann et al, 1998;Mech, 2003;Sidorovich et al, 2003) although the proportion of beaver in the wolf diet was seldom as high as in Latvia.…”
Section: Discussionmentioning
confidence: 98%